PELATIHAN DIGITAL BUSINESS BAGI CALON ENTREPRENEUR MUDA KOTA LHOKSEUMAWE DI MASA COVID-19 - Falahuddin Falahuddin; Fuadi Fuadi; Munandar Munandar; Devi Andriyani; Arliansyah Arliansyah (Jurnal Pengabdian Masyarakat Nusantara, 2021)
This service will provide an overview of entrepreneurship of small and medium enterprises using digital technology. From all points of view, be it motivation, business opportunities or ideas, as well as business rules according to sharia. During the current Covid-19 pandemic, it is very demanding for young people who already have business plans to adopt digital business tools more quickly to survive and develop in the new normal era. Therefore, prospective young entrepreneurs have great potential to be prepared to become excellent entrepreneurs, who will not only be economically independent, but will also develop regional economic potential which in turn will have a positive impact on the national economy. The purpose of this service is to overcome the problem of unemployment by the younger generation. The solutions we provide are in the form of training and providing motivation to develop and provide basic techniques for doing digital business, and do not forget to provide understanding to aspiring young entrepreneurs about doing business in an Islamic way as a form of development of the nation's.